Arabic Listening Comprehension Test Questions for Beginner Level Based on Competency Standards (ACTFL) - Mahmudi, Ihwan; Irfanudin, Arif; Hendri, Moh; Thoyib, Muhamad Luthfi (STAI Miftahul Ula Nganjuk, 2024)
This study aims to explore the use of ACTFL standards in Arabic language listening comprehension tests at the Novice level. The ACTFL standards for the Novice level are divided into three sub-levels: Novice High, Novice Mid, and Novice Low. This research employs a qualitative approach through literature review, analyzing the